2020
DOI: 10.5194/hess-2020-417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel analytical approach for the simultaneous measurement of nitrate and DOC in soil water

Abstract: Abstract. In this paper, we present a novel approach, enabling the measurement of nitrate concentrations in natural soil porewater containing natural soil dissolved organic carbon (DOC). The method is based on UV absorbance spectroscopy, combined with fluorescence spectroscopy, for simultaneous analysis of DOC and nitrate concentrations. The analytical procedure involves deduction of the absorption caused by the DOC from the total absorbance in the UV range that is attributed to both DOC and nitrate in the wat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Reply to comment 6: The presented methods require site-specific calibration, to overcome the interference on the nitrate's absorbance spectrum, caused by the local DOC chemical composition in the soil. As shown in the previous work of Yeshno et al, (2019) the optical characteristics of DOC may differ from site to site, and as such compensation of interference from DOC cannot be associated only with its concentration and should account for its local chemical and optical characteristics as well. Most of the known standard, common methods to deal with the absorption caused by DOC (as detailly described under reply to comment 2 and comment 5) do not provide a site-specific solution for the local DOC, and as such was less suitable for in-situ, porewater analyses.…”
Section: Interactive Commentmentioning
confidence: 92%
See 2 more Smart Citations
“…Reply to comment 6: The presented methods require site-specific calibration, to overcome the interference on the nitrate's absorbance spectrum, caused by the local DOC chemical composition in the soil. As shown in the previous work of Yeshno et al, (2019) the optical characteristics of DOC may differ from site to site, and as such compensation of interference from DOC cannot be associated only with its concentration and should account for its local chemical and optical characteristics as well. Most of the known standard, common methods to deal with the absorption caused by DOC (as detailly described under reply to comment 2 and comment 5) do not provide a site-specific solution for the local DOC, and as such was less suitable for in-situ, porewater analyses.…”
Section: Interactive Commentmentioning
confidence: 92%
“…Lastly, none of the presented methods mentions the necessity for site-specific calibration. As shown previously in a research made by the author of this paper, due to the variability in the optical absorption characteristics of the DOC found at different agricultural sites, a site-specific calibration is required to perform adequate calibration for nitrate (Yeshno et al, 2019). The method described is based on preliminary sample chemical analyses of the DOC found in each site porewater, and obtaining a calibration equation that is dealing with the absorption/fluorescence characteristic found at each study site.…”
Section: Authors Replymentioning
confidence: 99%
See 1 more Smart Citation
“…This data is under preparation and we hope to publish it soon. Note that lengthy field observations of nitrate measurement by spectral analyses when reduction of DOC interference was done by a site-specific algorithm, showed that once calibration was obtained it remained valid for a prolonged time interval (2 years) (Yeshno et al, 2019). This implies that the chemical composition of the DOC and thus its spectral interference in the UV range fairly stable over time, and as such allow continuous reading of nitrate by spectral techniques.…”
Section: Specific Commentsmentioning
confidence: 99%